Association of controlling nutritional status score and long-term mortality in acute pulmonary embolism - Kalkan, Kamuran; Tunca, Cagatay; Tanik, Veysel Ozan (Biomedical papers, 2025)
Background and Aims. Pulmonary embolism (PE) is a life-threatening condition with significant short- and long-term mortality risk. Although existing risk stratification models focus on short-term outcomes, the role of nutritional status in predicting long-term mortality remains underexplored. This retrospective study investigated the prognostic value of the Controlling Nutritional Status (CONUT) score, a composite index derived from serum albumin, total cholesterol, and lymphocyte counts. Methods. A total of 274 patients with confirmed PE were treated at a tertiary care center between January 2021 and March 2023. The primary endpoint was long-term all-cause mortality, as assessed using hospital records and follow-up interviews. Results. Multivariate analysis identified the CONUT score as an independent predictor of mortality (odds ratio [OR], 1.298; 95% confidence interval [CI], 1.066-1.580; P=0.009). A cut-off score of 2.5 demonstrated high prognostic accuracy (AUC, 0.844; sensitivity, 89%; specificity, 72%). Patients with higher CONUT scores exhibited increased inflammatory marker levels, lower serum albumin levels, and worse outcomes. Conclusion. These findings highlight CONUT score as a simple and cost-effective tool for assessing nutritional and inflammatory status, enabling improved long-term risk stratification in patients with PE. Future studies should validate these results in diverse populations and evaluate the impact of targeted nutritional and anti-inflammatory interventions on patient outcomes.
Keywords: pulmonary embolism; controlling nutritional status score; CONUT score; long-term mortality